How to Buy Pest Control Services - Philip G. Koehler; Roberto Pereira (EDIS)
Pest control, like any kind of business, is a joint venture between the company and the customer. As with many businesses, customers may have difficulty judging whether they have received the most skilled efforts for their money. This 4-page fact sheet should help customers objectively look at the service they are buying to determine its merit. Written by P. G. Koehler and published by the UF Department of Entomology and Nematology, July 2013. This fact sheet updates a chapter of SP134: Pests in and around the Florida Home, which is available from the IFAS Extension Bookstore.